2018
DOI: 10.1248/bpb.b17-00949
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Ge-132, a Synthetic Organic Germanium, on Cultured Mammalian Cells

Abstract: Ge-132 is a synthetic organic germanium that is used as a dietary supplement. The antioxidant activity of Ge-132 on cultured mammalian cells was investigated in this study. First, Ge-132 cytotoxicity on mammalian cultured cells was determined by measuring lactate dehydrogenase (LDH) levels. Ge-132 had no cytotoxic effect on three different cell lines. Second, the cell proliferative effect of Ge-132 was determined by measuring ATP content of whole cells and counting them. Ge-132 treatment of Chinese hamster ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
0
23
0
5
Order By: Relevance
“…The results confirmed that THGP also significantly suppresses cell death due to prolonged oxidative stress and indicate that THGP exerts an inhibitory effect on oxidative stress-induced cell death. It has been reported that THGP suppresses cell death caused by oxidative stress 28 , and Wada et al . found that THGP (Ge-132) exerts a cell proliferative effect by increasing the intracellular ATP content.…”
Section: Results and Disccusionmentioning
confidence: 99%
“…The results confirmed that THGP also significantly suppresses cell death due to prolonged oxidative stress and indicate that THGP exerts an inhibitory effect on oxidative stress-induced cell death. It has been reported that THGP suppresses cell death caused by oxidative stress 28 , and Wada et al . found that THGP (Ge-132) exerts a cell proliferative effect by increasing the intracellular ATP content.…”
Section: Results and Disccusionmentioning
confidence: 99%
“…This study demonstrates that THGP does not influence tyrosinase activity or the expression of genes involved in melanogenesis (Figure 5). In addition, previous studies have demonstrated that THGP exerts antitumor and antioxidant effects; thus, the side effects of THGP are likely limited [39,40,41,42]. Furthermore, because THGP did not affect cell proliferation at concentrations up to 5000 μM, THGP is considered safe up to this concentration (Figure 3).…”
Section: Discussionmentioning
confidence: 95%
“…Generally, the immunostimulation property of organic germanium is deemed to be the foundation of its various therapeutic effects, such as anticancer, antiaging, antiviral and antiinflammatory effects-areas in which immune function plays a key role. The immune function activation mechanism of organic germanium is established by enriching the oxygen supply [48,76,77], detoxifying heavy metal elements [48,[78][79][80], scavenging reactive oxygen species (ROS) [81][82][83] and increasing reduced glutathione (GSH) levels [81,84]. El-Din [85] reported that organic germanium showed radical scavenging activity immediately after tumor inoculation and γ-irradiation exposure, resulting in the suppression of tumor growth and in the reduction of cellular injury from γ-irradiation-induced toxicity, which were attributable to the inhibition of the cascade reaction of membrane lipid peroxidation.…”
Section: Plos Onementioning
confidence: 99%